DETERMING THE COMPENSATING ACTION OF COPPER AFTER SINTERING OF POWDER METALLURGICAL STRUCTURAL STEELS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper studies the dimensional changes during sintering of steel powders structural materials alloying with a 2,5 percents copper compound. Studied were three types of steel powders – NC 100.24; SC100.26 and ASC 100.29. Carbon concentration in the test pieces is between 0,2 and 0,8 percents, and their density between 6,2 and 7,0 grams per cubic centimeter.   Presented  are graphical relationships of the dimensional changes depending on the carbon concentration in the tested samples and their density.